Evidence in action between science and society constructing, validating and contesting knowledge - Ehlers, Sarah 1982-; Esselborn, Stefan (Routledge, Taylor & Francis Group, 2023)
"This volume is an interdisciplinary attempt to insert a broader, historically informed perspective into current political and academic debates on the issue of evidence and the reliability of scientific knowledge. Evidence in Action is the perfect resource for all those interested in the relationship between science, technology, and the role of knowledge in society"--
Literaturangaben. - Index
Keywords: Wissensvermittlung; Beweis; Gesellschaft; Wissenschaft; Wissenschaftskommunikation; Science / Social aspects; Evidence; Knowledge, Theory of; Science and civilization; Aufsatzsammlung